PENERAPAN APLIKASI MARBEL MATEMATIKA SD KELAS V UNTUK MENINGKATKAN SEMANGAT DAN HASIL BELAJAR SISWA - Siti Nur Afida Tsani; Kristina Gita Permatasari (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This research focuses on utilizing the Marbel Math SD application to enhance students' motivation and learning outcomes at the Elementary School level through the Research and Development (R&D) method. Marbel Math SD, as a learning innovation, has been developed with consideration for the elementary school mathematics curriculum and relevant learning theories. The development process involved initial design, content validation by experts, and limited testing on elementary school students. After the revision phase, the application was implemented in the experimental group, and learning outcomes as well as motivation were measured in the evaluation phase. The research results indicate a significant improvement in the learning outcomes and motivation of students using the Marbel Math SD application. Positive feedback from students and teachers demonstrates the favorable reception of this learning innovation. The application's implementation has a positive impact on math instruction in elementary schools, highlighting the effectiveness of interactive and enjoyable learning methods.